THE EFFECT OF PH ON KAOLINITE DISSOLUTION RATES AND ON ACTIVATION ENERGY - Ganor J.; Mogollon J.L.; Lasaga A.C. (My University, 1995)
Experiments measuring kaolinite dissolution rates were carried out using a stirred-flow reactor at temperatures of 25, 50, and 80°C and in the pH range 2 to 4.2. All experiments were conducted under far-from-equilibrium conditions (ΔG < -2.9 kcal/mol) and with minimum potential catalysts or inhibitors present in the solution. Therefore, the changes in the dissolution rates should be dominantly a function of the pH and the temperature. At 25 and 50°C the dissolution rate is independent of pH in the pH range 2 to 3, while at 80°C the dissolution rate is proportional to a0.4+/-0.2H+. The same proportionality of the rate toa0.4+/-0.14H+ was found at 25 and 50°C in the pH range of 3 to 4. In contrast to the results of previous studies, between pH 3 and 4 there is little or no difference between the pH reaction orders at 25 and 50°C (and also no difference at 80°C, based on previous studies. The similarity of reaction orders at different temperatures suggests that there is no pH effect on the activation energy of the kaolinite dissolution reaction, within the analytical error of our data. Using all the pH and temperature data, the activation energy obtained is 7.0 +/- 1.1 kcal/mol.